(untitled) (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. Introduzione - 2. L’obiettivo dell’integrazione e le nuove generazioni - 3. L’appannamento dell’obiettivo - 4. La via per uscire dalla crisi … - 5. … e i giovani - 6. Osservazioni finali: la stella polare. European Integration, Youth and the Social Doctrine of the Catholic Church ABSTRACT: This article deals with the topic of European integration from the point of view of the Social Doctrine of the Catholic Church, that is the part of the Teaching that focuses on the res publica. With a particular regard to the relationship between youth and European Union the article gives an analysis of the goals the European integration and the legitimation crisis of the Union’s institutions. As a possible way out of this crisis it suggests a re-focalisation of the “federalizing process” on the centrality of the human person and a valorisation of the fraternitas principle.